2010
DOI: 10.1109/tit.2010.2040965
|View full text |Cite
|
Sign up to set email alerts
|

Error Rates of the Maximum-Likelihood Detector for Arbitrary Constellations: Convex/Concave Behavior and Applications

Abstract: Motivated by a recent surge of interest in convex optimization techniques, convexity/concavity properties of error rates of the maximum likelihood detector operating in the AWGN channel are studied and extended to frequency-flat slow-fading channels. Generic conditions are identified under which the symbol error rate (SER) is convex/concave for arbitrary multi-dimensional constellations. In particular, the SER is convex in SNR for any one-and two-dimensional constellation, and also in higher dimensions at high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 41 publications
3
84
0
2
Order By: Relevance
“…R ECENTLY, signal and power randomization approaches have received considerable interest in the literature [1]- [5]. Several papers have addressed different aspects of the jammer power randomization/allocation problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…R ECENTLY, signal and power randomization approaches have received considerable interest in the literature [1]- [5]. Several papers have addressed different aspects of the jammer power randomization/allocation problem.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, jamming at the maximum available power limit is shown to be more advantageous beyond that critical value. This discussion is extended from binary modulations to arbitrary signal constellations in [5] by concentrating on the ML detection case in an additive white Gaussian noise (AWGN) channel. It is stated that the symbol error rate (SER) performance of the target receiver can be degraded via appropriate power/time sharing under a fixed average jammer noise power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a DMT perspective, the MIMO wiretap channel is equivalent to a reduced MIMO channel with (N t − N e ) and N m transmit and receive antennas, respectively. As the error probability is generally log-concave [26], [27], the diversity gain is an increasing function in SNR. Therefore, the finite-SNR secrecy diversity gain d s is equal to zero if N e ≥ N t .…”
Section: A Backgroundmentioning
confidence: 99%
“…It is shown that the average probability of error is a nonincreasing convex func tion of the signal power when the channel has a continuously differentiable unimodal noise probability density function (PDF) with finite variance. This discussion is extended from binary modulations to arbitrary signal constellations in [4] by concentrating on the maximum likelihood (ML) detection for AWGN channels. It is proven that an average power-limited transmitter cannot improve its error performance via time sharing between different power levels in low dimensions (I-D and 2-D) as opposed to the situation for some M-D constellations, M � 3.…”
Section: Introductionmentioning
confidence: 99%